Haunted Geographies and Partitioned Selves : Memory, Nostalgia, and Decolonial Desire in Bengali Films Bishorjon and Mati - Baishali Deb Roy (ILN Journal: Indian Literary Narratives, 2025)
This article examines how the Partition of Bengal is depicted in the films Kaushik Ganguly's Bishorjon (2017) and Leena Gangopadhyay’s Mati (2018) as a real and ongoing trauma that continues to influence memory, emotions, and locations, rather than merely as a historic break. The films' emphasis on female lead characters positions them as significant cultural memory bearers, whose emotional experiences stand in for ongoing trauma and intergenerational healing. The study also looks at homes, borders, and rivers as problematic places, landscapes that bear the scars of colonialism and concerns from the postcolonial era. These locations are ephemeral, replete with nostalgia, displacement, and spectral recollections of a Bengal that was once united. The study makes the case that both movies convey emotional maps of loss, nostalgia, and a desire for decolonization. They question strict nationalist histories and highlight a shared, changing cultural identity that goes beyond political divisions and time limits.